2022
DOI: 10.1093/gigascience/giad005
|View full text |Cite
|
Sign up to set email alerts
|

Genome assembly of Musa beccarii shows extensive chromosomal rearrangements and genome expansion during evolution of Musaceae genomes

Abstract: Background Musa beccarii (Musaceae) is a banana species native to Borneo, sometimes grown as an ornamental plant. The basic chromosome number of Musa species is x = 7, 10, or 11; however, M. beccarii has a basic chromosome number of x = 9 (2n = 2x = 18), which is the same basic chromosome number of species in the sister genera Ensete and Musella. Musa beccarii is in the section Callimusa, which is sister to the section Musa. We generated a high-quality chromosome-scale genome assembly of M. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…Within the three haploid assemblies, 256.48 Mb (53.76%), 258.29 Mb (54.14%), and 258.84 Mb (55.13%) of repetitive regions were identified ( Table S3 , see online supplementary material), similar to those in other banana genomes (e.g. M. acuminata : 52.62% [ 7 ]; M. beccarii : 55.99% [ 12 ]). Among them, the most abundant repetitive sequences were long terminal repeats (LTRs), which accounted for 36.36%, 35.44%, and 33.53% of the BXJ1, BXJ2, and BXJ3 assemblies, respectively ( Table S3 , see online supplementary material).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Within the three haploid assemblies, 256.48 Mb (53.76%), 258.29 Mb (54.14%), and 258.84 Mb (55.13%) of repetitive regions were identified ( Table S3 , see online supplementary material), similar to those in other banana genomes (e.g. M. acuminata : 52.62% [ 7 ]; M. beccarii : 55.99% [ 12 ]). Among them, the most abundant repetitive sequences were long terminal repeats (LTRs), which accounted for 36.36%, 35.44%, and 33.53% of the BXJ1, BXJ2, and BXJ3 assemblies, respectively ( Table S3 , see online supplementary material).…”
Section: Resultsmentioning
confidence: 57%
“…Since then, the DH-Pahang genome has been improved twice [ 6 , 7 ]. Moreover, other Musa genomes, for instance M. balbisiana , Musa itinerans , M. schizocarpa , Musa troglodytarum , and Musa beccarii , have already been reported during the past decade [ 2 , 8 12 ]. These high-quality banana genomes have provided necessary and valuable resources for further research on evolution of Musa genus, as well as domestication and breeding of banana.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is currently a challenge to obtain an accurate genome size with only short whole genome sequencing reads [42,43], which is also true for N. mirabilis in this study. Although both KmerGenie and GenomeScope estimated comparable genome sizes at a k-mer of 99 with 791,766,648 bp and 774,029,535 bp, respectively, we observed that the estimated genome size was affected by increasing k-mer from 17 to 71 in GenomeScope [26].…”
Section: Limitationsmentioning
confidence: 99%
“…JAPMAH000000000.1. All additional supporting data are available in the GigaScience repository, GigaDB [ 73 ].…”
Section: Data Availabilitymentioning
confidence: 99%